2016
DOI: 10.1002/pssb.201600461
|View full text |Cite
|
Sign up to set email alerts
|

Exciton binding energy in coupled double zinc blende GaN/InGaN quantum well

Abstract: In this work, the study of the 1s‐like exciton states and binding energy is presented for coupled double zinc blende GaN/InGaN quantum wells. The effective mass approximation and a variational procedure are the key theoretical tools used. The significant role of the position‐dependent effective mass is highlighted. It is found that the correct inclusion of position‐dependent masses is the cause of a noticeable difference in exciton energies with respect to the use of constant effective mass. In addition, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…However, obtaining high-quality AlGaN with high Al content and InGaN with high In content, commonly used as active media for optoelectronic devices, is quite difficult. Recently, III-nitride-based nanostructures such as quantum dots and nanowires (NWs) have been extensively investigated to extend their emission wavelengths. GaN NWs formed on Si(111) were used as active media for optical devices because they showed high exciton-binding energies and relatively high carrier mobilities. The most well-known approach for the formation of GaN NWs is the vapor–liquid–solid (VLS) process, in which a metallic catalyst acts as seeds to promote the formation of anisotropic NWs. , However, forming high-quality GaN NWs remains difficult because of the contamination originated from metal catalysts. Several research groups have reported catalyst-free or self-catalyst GaN NWs using VLS or Volmer–Weber modes to reduce the chemical contamination caused by metallic catalysts. However, because of the large difference in material parameters between GaN and Si, including the lattice constants and thermal expansion coefficients, methods for forming high-crystal-quality GaN NWs remain in development. That is, catalyst-free GaN NWs on Si substrates show various shapes and many structural defects, including stacking faults. , From this consideration, it is first necessary to form GaN NWs with a high crystal quality and uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…However, obtaining high-quality AlGaN with high Al content and InGaN with high In content, commonly used as active media for optoelectronic devices, is quite difficult. Recently, III-nitride-based nanostructures such as quantum dots and nanowires (NWs) have been extensively investigated to extend their emission wavelengths. GaN NWs formed on Si(111) were used as active media for optical devices because they showed high exciton-binding energies and relatively high carrier mobilities. The most well-known approach for the formation of GaN NWs is the vapor–liquid–solid (VLS) process, in which a metallic catalyst acts as seeds to promote the formation of anisotropic NWs. , However, forming high-quality GaN NWs remains difficult because of the contamination originated from metal catalysts. Several research groups have reported catalyst-free or self-catalyst GaN NWs using VLS or Volmer–Weber modes to reduce the chemical contamination caused by metallic catalysts. However, because of the large difference in material parameters between GaN and Si, including the lattice constants and thermal expansion coefficients, methods for forming high-crystal-quality GaN NWs remain in development. That is, catalyst-free GaN NWs on Si substrates show various shapes and many structural defects, including stacking faults. , From this consideration, it is first necessary to form GaN NWs with a high crystal quality and uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent advancement, Rath and collaborators proposed a new position-dependent mass system suitable for applications in semiconductor physics [8]. The concept of position-dependent mass (PDM) has also been used to investigate quantum dots, quantum wires and quantum wells [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…For examples, GaN, AlGaN, and InGaN NWs formed on Si substrates have been investigated for the applications of light-emitting diodes and photosensors [7,8]. Theoretically, GaN NWs formed on Si (111) can be used as an active medium for optoelectronic devices due to their high exciton binding energy and relatively fast carrier mobility [9,10]. One of the most well-known approaches for the formation of Si-based GaN NWs is vapor-liquidsolid (VLS) process, using metal catalysts acting as nucleation seeds of NWs [11,12].…”
Section: Introductionmentioning
confidence: 99%